Modified surface of duplex stainless steel using TIG torch melting and diffusion techniques - Maleque, Md. Abdul; Paijan, Lailatul Harina (2017)
Surface modification of duplex stainless steel (DSS) is important to make this material suitable for tribological applications. Melting technique using tungsten inert gas (TIG) torch and diffusion process using gas nitriding are the effective procesess to meet this requirement with simple and cost effective techniques. For TIG torch melting techniques, the reinforced composite coating is developed on DSS with the preplacement of SiC embedded in DSS using simple TIG torch technique. The hard layer produce the dense coating with good metallurgical bonding to the base material. In diffusion process, heat catalyst is used for the decomposition of ammonia into nascent nitrogen to diffuse into DSS surface. Hard surface layer is developed using this technique.